A simple spot test quantification method to determine formaldehyde in aqueous samples - Amara Dar; Umer Shafique; Jamil Anwar; Waheed-uz-Zaman; Arooj Naseer (Journal of Saudi Chemical Society)
A simple, accurate, and economical method has been proposed to measure formaldehyde in aqueous samples. The method is based on quantification of classical chromotropic acid – formaldehyde violet spots developed on TLC. Different parameters such as concentration of chromotropic and sulfuric acid, time of heating and order of application of reagents have been studied to find out the optimum working procedure. Spots have been quantified by scanning the spotted TLC and analyzing the image in computer with Visual Basic 6.0 based graphic application. The study consisted of developing an appropriate calibration line, analyzing artificial and real samples, and comparing the new method with a standard spectrophotometric method (NIOSH Method-3500, 1994). It has been concluded that the present method had the capability for measuring formaldehyde in aqueous samples at trace level with high precision and accuracy, particularly when dealing with turbid and small volume samples where the standard method failed.